A male case of dermatofibrosarcoma protuberans in the breast presenting as gynecomastia - Vučaj-Ćirilović Viktorija; Vuković Miloš; Boban Jasmina; Šolajić Nenad; Ranisavljević Milan; Prvulović-Bunović Nataša (Vojnosanitetski Pregled)
Introduction. Dermatofibrosarcoma protuberans (DFSP) is a very rare mesenchymal tumor that accounts for approximately 0.1% of all malignancies. It is a locally aggressive fibrous tumor, with a high recurrence rate, which sometimes gives rise to distant metastases, usually to the bones and lungs. DFSP usually occurs on the trunk and extremities with only a small number of cases in the breast, especially in men. Case report. We presented a rare case of DFSP in the male breast. A 66-year-old man presented with gynecomastia of the left breast. The diagnostic work-up comprised of clinical examination, ultrasonography, core biopsy, and mammography. Immunohistochemistry revealed diffuse and strong positivity for vimentin, CD99, and CD34, while the tumor cells were completely negative for keratin, S100 protein, STAT6, CD31, and factor VIII, highly suggestive for DFSP. Subsequently, a radical mastectomy was performed and preoperative diagnosis of DESP was confirmed by pathological examination and immunohistochemistry. The patient was still disease-free six months after the surgical treatment. Conclusion. DFSP is a soft tissue sarcoma that rarely occurs in the breast, especially in men. The most common clinical presentation in the breast is a mass with extensive nodules on the surface, but it can also be presented as gynecomastia, as in our case. The diagnosis of DFPS is based on anatomopathology with immunohistochemistry analysis since there are no specific imaging features for this rare entity. Surgical excision with wide and negative margins is optimal for reducing the risk of recurrence.